Suitability of Different Extractants for Estimation of Cationic Micronutrients in Lateritic Soils of West Bengal - Nisab, Mohammed C. P.; Ghosh, G. K. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at Institute of Agriculture (Palli Siksha Bhavana), Visva-Bharati West Bengal, India during 2019–20 to evaluate the extractability of different extractants for extraction of cationic micronutrients in lateritic soils of West Bengal under rice based cropping system. Fifty surface (0‒15 cm) samples were collected from rice-based cropping systems from five different blocks of Birbhum district. The pH of the soil was found extremely acidic to slightly acidic. The organic carbon content (%) were low to medium range. Among major nutrients available phosphorus and sulphur showed deficiency under study area. The micronutrients cations were extracted from the soils using five different extractants, namely, Mehlich 3, HCl, AB-DTPA and the conventional extractant DTPA. The greatest mean concentration for all the micronutrients was obtained by Melich 3 extractant followed by HCl whereas the lower values were obtained when DTPA extractant used. Themagnitude of extraction for all cationic micronutrients was Mehlich 3>HCl>AB-DTPA>DTPA. Melich 3 has a higher extractability due to its high pH and ability to displace exchangeable cations due to the presence of the NH4+ ion in the extractant. The low extractability of the DTPA extractant may be due to disruption of metal-chelate equilibria in acidic soils. A higher positive significant correlation observed among the extractants from the study indicated that, they were able to extract the micronutrients from remarkably similar pools.